Identification of anti‐cancer chemical compounds using Xenopus embryos. Issue 6 (12th May 2016) - Tanaka, Masamitsu; Kuriyama, Sei; Itoh, Go; Kohyama, Aki; Iwabuchi, Yoshiharu; Shibata, Hiroyuki; Yashiro, Masakazu; Aiba, Namiko
Abstract : Cancer tissues have biological characteristics similar to those observed in embryos during development. Many types of cancer cells acquire pro‐invasive ability through epithelial–mesenchymal transition (EMT). Similar processes (gastrulation and migration of cranial neural crest cells [CNCC]) are observed in the early stages of embryonic development in Xenopus during which cells that originate from epithelial sheets through EMT migrate to their final destinations. The present study examined Xenopus embryonic tissues to identify anti‐cancer compounds that prevent cancer invasion. From the initial test of known anti‐cancer drugs, AMD3100 (an inhibitor of CXCR4) and paclitaxel (a cytoskeletal drug targeting microtubules) effectively prevented migration during gastrulation or CNCC development. Blind‐screening of 100 synthesized chemical compounds was performed, and nine candidates that inhibited migration of these embryonic tissues without embryonic lethality were selected. Of these, C‐157 (an analog of podophyllotoxin) and D‐572 (which is an indole alkaroid) prevented cancer cell invasion through disruption of interphase microtubules. In addition, these compounds affected progression of mitotic phase and induced apoptosis of SAS oral cancer cells. SAS tumors were reduced in size after intratumoral injection of C‐157, and peritoneal dissemination of melanoma cells and intracranial invasion of glioma cells were inhibited by C‐157 and D‐572. When the other analogues of these chemicals were compared, those with subtle effect on embryos were not tumor suppressive. These results suggest that a novel chemical‐screening approach based on Xenopus embryos is an effective method for isolating anti‐cancer drugs and, in particular, targeting cancer cell invasion and proliferation. Abstract : Cancer tissues have biological characteristics similar to those observed in embryos during development. A novel chemical‐screening approach based on Xenopus embryos in this study is an effective method for isolating anti‐cancer drugs especially targeting cancer cell invasion and proliferation.